2018
DOI: 10.3390/s18051577
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Gait Variable Estimation Using Wearable Sensors after Unilateral Total Knee Arthroplasty

Abstract: Total knee arthroplasty is a common surgical treatment for end-stage osteoarthritis of the knee. The majority of existing studies that have explored the relationship between recovery and gait biomechanics have been conducted in laboratory settings. However, seamless gait parameter monitoring in real-world conditions may provide a better understanding of recovery post-surgery. The purpose of this study was to estimate kinematic and kinetic gait variables using two ankle-worn wearable sensors in individuals afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 16 publications
(26 reference statements)
0
20
0
Order By: Relevance
“…A triaxial accelerometer was the most commonly used sensor incorporated in the functional assessment subgroup, with 15 of 16 studies (94%)8 19–32 using the sensor alone or in combination with other instrumentation. Seven of the functional studies exclusively used triaxial accelerometers as the means for data collection during functional analysis 8 20–22 24 28 31. Three studies used IMUs with an integrated triaxial accelerometer and triaxial gyroscope,19 27 29 while three others recorded gait with a 9 df IMU integrating triaxial accelerometer, gyroscope and magnetometer 25 26 30.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A triaxial accelerometer was the most commonly used sensor incorporated in the functional assessment subgroup, with 15 of 16 studies (94%)8 19–32 using the sensor alone or in combination with other instrumentation. Seven of the functional studies exclusively used triaxial accelerometers as the means for data collection during functional analysis 8 20–22 24 28 31. Three studies used IMUs with an integrated triaxial accelerometer and triaxial gyroscope,19 27 29 while three others recorded gait with a 9 df IMU integrating triaxial accelerometer, gyroscope and magnetometer 25 26 30.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies (13 studies, 81%)8 19–22 24–30 33 included pre-operative data collection with repeated tests at one or more time points up to 1-year post-operatively, most frequently up to 6 weeks after surgery. Three studies collected data at an unspecified point any time greater than 6 months post-operatively 23 31 32…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Rodríguez-Martín et al ( 2017 ) used a triaxial accelerometer and machine learning to better detect freezing of gait in patients with Parkinson's disease as opposed to self-reported questionnaires, and Na and Buchanan ( 2020 ) validated the use of wearable technology against self-reported measures for stability in individuals with knee OA. Our previous work estimated kinematic and kinetic gait parameters from inertial gait variables using wearable devices (Youn et al, 2018 ), but the efficacy of inertial gait variables in determining self-reported patient outcomes and functional performance based measures in individuals post-TKA has yet to be explored. While it is often suggested that movement patterns are associated with functional ability and quality of life, few studies have evaluated the relationship between objective measures of gait and clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%